Toothbrush 2-in-1 / Alice Evana Robert ... [et al.] - Robert, Alice Evana; Obaun, Latijah; Stephen, Staffy; Bidder, Christy (2021)
The innovative 2-in-1 toothbrush is served both the functions of toothbrush and toothpaste. These two items are some of the items we use in our everyday life and when we travel. When traveling, we tend to pack mundane items such as toothbrush and toothpaste. We often overlook, and sometimes we even feel stressful. We can easily purchase these items at the destination if we forget to pack them, but that it will be an unnecessary additional expense and another task to accomplish upon arriving at the destination. Another option is to pack the large tube of toothpaste we have in the washroom and use in our every life, plus our regular toothbrush, but then there are the 3-1-1 liquid rules to consider (particularly for international travel). When travelling or hiking for days, we pack other important items first. Later, we pack toothbrush and toothpaste separately, and it consume space in our in the hiking backpacks. It can be a huge annoyance when one could not find toothbrush or toothpaste hidden among clothes, pants, jackets and other trekking necessities after a long trek. Thus, it would definitely be nice to have 2-in-1 toothbrush that can be easily stored in one specific section of the backpack. For long flights that involve long airport layovers, a convenient access to toothbrush and toothbrush can be useful to make us feel refreshed and clean in the mouth. Travel-sized toothpaste and toothbrush are widely available at the supermarkets and pharmacies. While the size is convenient, the the innovated product of 2-in-1 toothbrush can be beneficial. The following sections will present the objectives, novelty, special criteria, impact/usefulness and product specification of the proposed 2-in-1 toothbrush.